Review of Research on Stress and Mindfulness: A Bibliometric Analysis - Prof. Shikha Mann, Dr. Natashaa Kaul, Dr. Surya Rashmi Rawat (International Journal of Advanced Science and Technology, 2020)
After 2008, there has been increase in research on mindfulness and stress. Researchers have been examining mindfulness as one of the strategies to manage stress. Many researchers have contributed to qualitative and empirical work in this area but needs to be complemented with a comprehensive analysis of the area’s literature especially in the area of management research since the topic explored from the medical, psychology, healthcare and other perspectives also. This study is an attempt to present an analysis of all the research work that has been done in the domain of “business, accounting and management” in past decade using bibliographic coupling, co-citation and co-occurrence analyses. VosViewer’s visualization tool was used for research. 103 publications in the area were collected as a sample using the Scopus database as a source for the years from 2008 to 2019 in the category of “business, management and accounting” to serve as a base to understand the research landscape. Prominent researchers are identified along with popularly cited papers and journals with major publications in the area.